LUNAR OCCULTATIONS of 18 STELLAR SOURCES from the 2.4 m Thai NATIONAL TELESCOPE - A. Richichi (2018)
© 2016. The American Astronomical Society. All rights reserved. We report further results from the program of lunar occultation (LO) observations started at the 2.4 m Thai National Telescope (TNT) in 2014. We have recorded LO events of 18 stellar sources, leading to the detection of four angular diameters and two binary stars. With two exceptions, these are first-time determinations. We could resolve angular diameters as small as 2 milliarcseconds (mas) and projected separations as small as 4 mas. We discuss the individual results, in the context of previous observations, when available. The first-time angular diameters for o Psc, HR 6196 and 75 Leo are in good agreement with expected values, while that of π Leo agrees with the average of previous determinations but has a higher accuracy. We find a new secondary in o Psc, as previously suspected from Hipparcos data. We also obtain an accurate measurement of the companion in 31 Ari, revealing inconsistencies in the currently available orbital parameters. The TNT, equipped with the fast ULTRASPEC imager, is the leading facility in Southeast Asia for high time resolution observations. The LO technique at this telescope achieves a sensitivity of i′ ≈ 10 mag, with a potential to detect several hundreds of LO events per year.